A Highly Sensitive and Stable SERS Sensor for Malachite Green Detection Based on Ag Nanoparticles In Situ Generated on 3D MoS2 Nanoflowers. Issue 1 (7th January 2020) - Jiang, Jiayu; Shen, Qihui; Xue, Peng; Qi, Hui; Wu, Yunpeng; Teng, Yifei; Zhang, Yuwan; Liu, Yan; Zhao, Xudong; Liu, Xiaoyang
Abstract: The hybrid plasmon composition based on MoS2 has been extensively studied as a higher disposition surface enhanced Raman scattering (SERS) substrate. In this paper, a novel silver nanoparticle based SERS substrate was developed via in situ microwave synthesis approach on a three dimensional (3D) MoS2 nanoflower (MoS2 NF/ Ag NPs). The prepared SERS sensor has strong SERS activity on malachite green (MG), the Raman enhancement factor (EF) is as high as 1.46×10 12 . The standard Raman signal peak of MG at 1618 cm −1 has a good linear relationship at 10 −12 ‐ 10 −2 mol⋅L −1 . The limit of detection (LOD) was calculated as approximately 10 −14 mol⋅L −1, which shows the good prospects for MG's microtests. In addition, the SERS sensor still shows good SERS performance stability after 112 days, which improves the shelf life of the SERS sensor and can be effectively applied to fishery water monitoring. Abstract : A novel silver nanoparticle based SERS substrate was developed via in situ microwave synthesis approach on a three dimensional (3D) MoS2 nanoflower (MoS2 NFs / Ag NPs).The prepared SERS sensor has strong SERS activity. The detection of MG was calculated as approximately 10 −14 mol⋅L −1, which shows the good prospects for MG's microtests. The Raman enhancement factor (EF) is 1.46×10 12 . The SERS sensor still shows good SERS performance stability after 112 days.